Equivalence Translation: The Student's Mastery In Translation Of Indonesian Idiomatic Expressions To English - Erika Sinambela; Carolina Carolina; Asima Situmorang (Jurnal Ilmu Sosial Mamangan, 2024)
The purpose of this study is to determine the students' proficiency with equivalency translation—the process of translating an Indonesian idiomatic expression into English. The population of the study was the fifth-semester students at the Faculty of Language and Art in Medan. The thirty students that make up the research sample were chosen at random for this study. A descriptive quantitative design is used in this study. Giving the students a translation test is the method utilized to gather data. To determine if the pupils are capable or not, the data was examined by providing the translation test score. According to the analysis's findings, 13 students (43%) and 17 students (57%) were unable to determine which English proverbs were most similar to Indonesian proverbs.